CURRENT TRENDS AND DEVELOPMENT FACTORS IN THE APPLICATION OF DIGITAL TECHNOLOGIES IN EDUCATION (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: This thesis presents a thorough analysis of the most recent developments and trends in the use of digital technology in education. It examines and discusses the effects of major trends in education, including mobile learning, gamification, artificial intelligence, virtual and augmented reality, online learning platforms, and adaptive learning systems. The thesis also examines development elements, such as funding, policy frameworks, teacher preparation, infrastructure, and pedagogical concerns that influence the adoption and integration of these technologies. The thesis provides insightful information about the changing landscape of digital education and its implications for educational stakeholders through an examination of recent research and case studies.